PENERAPAN MODEL PEMBELAJARAN KOOPERATIF MAKE A MATCH UNTUK MENINGKATKAN AKTIVITAS DAN HASIL BELAJAR BIOLOGI SISWA KELAS X.2 SMA NEGERI 10 PEKANBARU TAHUN AJARAN 2012/2013 - Darmawati '; Arnentis '; Sri Iryani (Biogenesis, 2013)
This study aimed to improve learning outcomes biological activity and X.2 grade students of SMA Negeri 10 Pekanbaru Academic Year 2012/2013 through the implementation of cooperative learning model make a match. This research is a classroom action research was conducted in October-November 2012. The subjects were students of SMAN 10 Pekanbaru X.2 class numbering 30 people consisting of 12 male students and 18 female students. The research instrument consists of learning tools and data collection instruments. Research procedure consists of the planning, implementation of action, observation and reflection. Parameter study consisted of student activities, teacher activities and learning outcomes. The results show the average activity in the first cycle is 81.91% (average) increase in cycle II with an average activity of students is 88.12% (excellent). Average absorption of the first cycle students is 66.81% (average) and increased in the second cycle with an average 82.16% (excellent).Mastery learning students in the first cycle is 63.33% (complete) and 36.67% (not finished), and the second cycle increased to 100% (complete). In cycle I, a group award for four groups earn great rewards and a group of super honored. In the second cycle all super group awarded. Activities of teachers in the first cycle with the average of 92.85% (excellent) on the second cycle increased to 100% (very good). From the results of this study concluded that the implementation of cooperative learning model Make A Match can enhance biological activity and learning outcomes of students in Grades X.2 SMA Negeri 10 Pekanbaru Academic Year 2012/2013.Keywords: Cooperative Models Make A Match, Activities and Learning Outcomes.